The Implementation of Constructivist Learning Methods on Student Activity - Khoir, Tita Syafa’atul; Bahtiar, Yuyun; Nisa, Khoirun; Huda, Saihul Atho Alaul; Zakaria, Ahmad Alex (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The constructivist method has the characteristics of student explanations originating from the teacher's general concepts. The constructivist method is a method taken from philosophy in the sense that students explain concepts that have been put forward by the teacher globally. In its application, Islamic Senior High School Al Ihsan Kalikejambon applies constructivist methods to its students with the aim of awakening the activeness within their students when the teaching and learning process takes place. The constructivist method, applied in the classroom through various models or types. A learning model with a constructivist method that suits the student's character can be applied maximally in the classroom. On the other hand, if the choice of constructivist methods in the classroom is not appropriate, then the teacher is required to look for other methods that are in line with student characteristics to generate activity in the classroom. For Islamic Senior High School Al-Ihsan Kaikejambon itself, it applies constructivist methods through the subject of moral beliefs. Moral beliefs which contain two elements, namely Theology and morals, can be understood by means or methods used which are constructivist or looking at the environment using the senses and processing it into new knowledge without having to get out of previously existing concepts. Every method applied, including constructivist methods, certainly experiences periods of resistance and support. The obstacles that exist are the different characteristics of students. and the support is that students become braver and enjoy learning, thereby creating an active and conducive class.